Factors that influence clinical trial participation for oncology patients in Australia: a scoping review - Zarnie Lwin; David Wyld; Elizabeth Ahern; Natasha Roberts; Kyung Ha You (BMJ Open)
Objectives Ensuring equity in clinical trials has been declared a global priority. Australia is competitive in the international clinical trial sphere. We aimed to explore factors that influence oncology clinical trial participation in Australia.Design Scoping review.Data sources On 27 May 2024, a systematic search using a predefined strategy was conducted across four electronic databases (Medline, CINAHL, EMBASE and Scopus), grey literature and hand searches.Eligibility criteria All cancer (haematological and non-haematological) clinical trials that discussed factors influencing participation in Australia were included. There were no language or age restrictions.Data extraction and synthesis Data were extracted using a predesigned extraction tool. Quantitative results were analysed using descriptive statistics. Qualitative data were synthesised using a framework method into four domains (1) patients, (2) healthcare professionals, (3) clinical trials and (4) health services.Results Of 1084 citations identified, 393 duplicates were removed. Of the 691 titles and abstracts screened, 54 articles underwent full-text review, and 42 articles were included in the final analysis. Key factors that influence clinical trial participation were identified across all domains, many consistent with the international literature. For example, while self-reported willingness emerged as a key facilitator across diverse patient groups, cohort studies revealed lower participation rates for migrant populations, older patients and those residing in regional areas. Importantly, we were also able to identify the foundations of an evidence base of interventions that directly support increased clinical trial participation.Conclusion This scoping review contributes new findings to a body of international literature, while contributing a unique Australian perspective. These findings establish the foundations of an evidence base that supports inclusive clinical trial participation.